Human TAF(II)130 Is a Coactivator for NFATp - Kim, Loree J. (American Society for Microbiology, 2001)
NFATp is one member of a family of transcriptional activators that regulate the expression of cytokine genes. To study mechanisms of NFATp transcriptional activation, we established a reconstituted transcription system consisting of human components that is responsive to activation by full-length NFATp. The TATA-associated factor (TAF(II)) subunits of the TFIID complex were required for NFATp-mediated activation in this transcription system, since TATA-binding protein (TBP) alone was insufficient in supporting activated transcription. In vitro interaction assays revealed that human TAF(II)130 (hTAF(II)130) and its Drosophila melanogaster homolog dTAF(II)110 bound specifically and reproducibly to immobilized NFATp. Sequences contained in the C-terminal domain of NFATp (amino acids 688 to 921) were necessary and sufficient for hTAF(II)130 binding. A partial TFIID complex assembled from recombinant hTBP, hTAF(II)250, and hTAF(II)130 supported NFATp-activated transcription, demonstrating the ability of hTAF(II)130 to serve as a coactivator for NFATp in vitro. Overexpression of hTAF(II)130 in Cos-1 cells inhibited NFATp activation of a luciferase reporter. These studies demonstrate that hTAF(II)130 is a coactivator for NFATp and represent the first biochemical characterization of the mechanism of transcriptional activation by the NFAT family of activators.